Overtime Wage Practices in Indonesia A Qualitative Analysis Based on Islamic Economic Law at PT. Agro Jaya Perdana - Alda Firdaus; Zaenal Abidin; Triyana Wulandari (Zabags International Journal of Islamic Studies, 2025)
The wage and overtime compensation system in Indonesia continues to face systemic challenges in ensuring fairness, transparency, and the protection of workers' rights. This study aims to examine the extent to which overtime wage practices at PT. Agro Jaya Perdana comply with Islamic economic law principles. Employing a qualitative approach with a case study strategy, the research collects data through field observations, in-depth interviews with eight key informants, and the analysis of company documents. Thematic analysis, supported by NVivo software, revealed six core themes: lack of formal employment contracts, limited worker understanding of wage calculation, disproportionate compensation relative to workload, absence of complaint mechanisms, the normalization of overtime as routine, and ethical disconnects between management and labor. These findings indicate that essential principles of Islamic economic law such as contract clarity, fair remuneration, and mutual consent are not adequately fulfilled. This article contributes to scholarly discourse by integrating normative Islamic legal perspectives with empirical labor realities, offering an evaluative framework based on maqasid al-shariah. The study provides practical implications for improving wage systems and strengthening Islamic legal literacy within industrial labor relations.